2018
DOI: 10.1371/journal.pone.0207301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing heart rate on finger photoplethysmography fitness index (PPGF) in subjects with implanted cardiac pacemakers

Abstract: Finger photoplethysmography (PPG) is a noninvasive method that measures blood volume changes in the finger. The PPG fitness index (PPGF) has been proposed as an index of vascular risk and vascular aging. The objectives of the study were to determine the effects of heart rate (HR) on the PPGF and to determine whether PPGF is influenced by blood pressure (BP) changes. Twenty subjects (78±8 years, 3 female) with permanent cardiac pacemakers or cardioverter defibrillators were prospectively recruited. HR was chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…There are other inflammatory mediators that can be assessed such as IL-6 and TNF- α . On the other hand, there are other available methods to assess arterial stiffness such as augmentation index and finger photoplethysmography fitness index (PPGF) [ 55 – 57 ]. However, in this review, we only focus on cfPWV and baPWV since both methods have been found to be associated with future CVD as mentioned earlier [ 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are other inflammatory mediators that can be assessed such as IL-6 and TNF- α . On the other hand, there are other available methods to assess arterial stiffness such as augmentation index and finger photoplethysmography fitness index (PPGF) [ 55 – 57 ]. However, in this review, we only focus on cfPWV and baPWV since both methods have been found to be associated with future CVD as mentioned earlier [ 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mediators of Inflammation [55][56][57]. However, in this review, we only focus on cfPWV and baPWV since both methods have been found to be associated with future CVD as mentioned earlier [9,12].…”
mentioning
confidence: 99%
“…The PPGF index was derived from an AC component of the PPG morphological changes and compared with a 19-year-old healthy reference (gender-specific) who was identified from the population. The details of the formula could be found in the previous study ( Aminuddin et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…PPG measures blood volume changes in the peripheral arterial bed via optical techniques in accordance with the contraction and relaxation of the heart. PPG values are affected by several parameters, such as arterial stiffness, resistance, pressure, and blood viscosity ( Aminuddin et al, 2018 ). There are several PPG indexes that have been introduced for the assessment of vascular function, such as stiffness index, reflection index, aging index, and second derivative of PPG ( Allen, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of HR towards PPG markers are still inconclusive. Because PPG markers had an association with arterial stiffness, it is speculated that HR may affect PPG markers [45]. The variation of the HR may influence the result of vascular markers and affect cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%